1996
DOI: 10.1097/00044067-199605000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Blood Analysis Using Point-of-Care Technology

Abstract: Rapid analysis of selected laboratory tests is essential in the management of critically ill patients. These tests facilitate accurate diagnosis of clinical problems and the initiation and evaluation of appropriate therapeutic interventions. Instruments are now available to perform analysis at a site near the patient, or "point-of-care" testing. These instruments incorporate electrochemical and optical sensors capable of providing information on multiple analytes from a small sample of whole blood. In this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Few studies exist examining agreement between glucometry and other methods of measuring glucose in critical care settings, and none were found that examine the question in a veterinary equine neonatal intensive care unit. Glucometry in human ICU/NICU studies is generally performed using capillary blood from finger or similar ‘sticks,’ while in most veterinary NICUs glucometry is performed using whole venous or arterial blood 2–4,6,7,9–12 . Studies of glucometry in the human ICU/NICU have shown that altered hemocrit (too large or too small), metabolic acidosis, systemic hypoperfusion and altered oxygen tensions (again, too large or too small) resulted in inaccuracies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies exist examining agreement between glucometry and other methods of measuring glucose in critical care settings, and none were found that examine the question in a veterinary equine neonatal intensive care unit. Glucometry in human ICU/NICU studies is generally performed using capillary blood from finger or similar ‘sticks,’ while in most veterinary NICUs glucometry is performed using whole venous or arterial blood 2–4,6,7,9–12 . Studies of glucometry in the human ICU/NICU have shown that altered hemocrit (too large or too small), metabolic acidosis, systemic hypoperfusion and altered oxygen tensions (again, too large or too small) resulted in inaccuracies.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose measurements in critically ill neonatal foals are usually performed using venous blood obtained by direct venipuncture (jugular vein or peripheral vein). Capillary blood is rarely used, which is different from human hospital critical care units 2–12 . Blood glucose in foals can be measured by using a reagent strip and glucometry, a multi‐electrode blood gas analyzer, or a serum/plasma chemistry analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…Use of a point‐of‐care analyzer (POCA) is now common in hospital emergency rooms and intensive or critical care units where blood gas (BG) or acid–base (AB) samples are collected and handled anaerobically until analysis is performed 1–5 . The samples are chilled if a delay of more than 15 minutes between collection and analysis is expected 2,6–9 .…”
Section: Introductionmentioning
confidence: 99%
“…Use of a point‐of‐care analyzer (POCA) is now common in hospital emergency rooms and intensive or critical care units where blood gas (BG) or acid–base (AB) samples are collected and handled anaerobically until analysis is performed 1–5 . The samples are chilled if a delay of more than 15 minutes between collection and analysis is expected 2,6–9 . If it is not feasible or possible to obtain an arterial sample, an anaerobic venous sample may be collected for AB determination since venous and arterial blood samples are equivalent for metabolic AB determinations 5,7,10–16 …”
Section: Introductionmentioning
confidence: 99%
“…These include point-of-care testing [8], high throughput drug discovery [9], detection of biological warfare agents [10], astrobiology [11] and others. Such applications of biosensors require high-density arrays of microvolume reaction vessels.…”
Section: Introductionmentioning
confidence: 99%